The Implemetasi Internet of Things dengan Menggunakan NodeMCU 8266 Pada Sistem Alat Bantu Komunikasi Lansia: Elderly individuals are susceptible to systemic and metabolic health problems, making it more difficult to perform daily activities. - Muslim, Moh Zaidul; Kurniawan, Edy; Riyanto, Didik (FORTEI Regional VII Jawa Timur, 2025)
Elderly individuals are susceptible to systemic and metabolic health problems, making it more difficult to perform daily activities. This research aims to determine how to create communication aid for the elderly based on internet of things. The method used in this study is planning, designing and testing communication aids. The planning stage starts with making the tool design, designing the circuit module and determining the electronic components. The design starts with making the frame, assembling the microcontroller circuit, assembling the frame with the microcontroller circuit and designing the software by creating a programming language on the Arduino Uno IDE. The results of the study show that the creation of communication aids for the elderly is done by designing an electronic circuit by integrating sensors with the ESP8266 Wifi module. The system design is carried out through the stages of identifying the needs of elderly users through interview studies, planning hardware and software designs, hardware and software designs, and integration stages with the Telegram application. The test results show that the tool can convey messages or notifications automatically real-timeAs long as it's connected to the internet no more than 70 meters, the device can respond quickly when the sender presses a button, and the recipient can receive a notification. The recipient can respond by replying via Telegram, while the sender can view the notification on the LCD screen. The communication tool still depends on the internet network and power supply.